The labor market impact of immigration in Western Germany in the 1990's - Francesco D'Amuri; Gianmarco I. P. Ottaviano; Giovanni Peri (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2008)
We adopt a general equilibrium approach in order to measure the effects of recent immigration on the Western German labor market, looking at both wage and employment effects. Using the Regional File of the IAB Employment Subsample for the period 1987-2001, we find that the substantial immigration of the 1990's had no adverse effects on native wages and employment levels. It had instead adverse employment and wage effects on previous waves of immigrants. This stems from the fact that, after controlling for education and experience levels, native and migrant workers appear to be imperfect substitutes whereas new and old immigrants exhibit perfect substitutability. Our analysis suggests that if the German labor market were as 'flexible' as the UK labor market, it would be more efficient in dealing with the effects of immigration.
Keywords: E24; F22; J61; J31; 330; Immigration; Skill Complementarities; Employment; Wages